Determinação de Chaveamento para Recomposição do Serviço em Redes de Distribuição de Energia Elétrica em Média Tensão Através de Métodos Baseado em Parâmetros de Sensibilidade - Silva Junior, José Luiz da (2012)
The reconfiguration of a distribution network is a change in its topology, aiming to provide specific operation conditions of the network, by changing the status of its switches. It can be performed regardless of any system anomaly. The service restoration is a particular case of reconfiguration and should be performed whenever there is a network failure or whenever one or more sections of a feeder have been taken out of service for maintenance. In such cases, loads that are supplied through lines sections that are downstream of portions removed for maintenance may be supplied by the closing of switches to the others feeders. By classical methods of reconfiguration, several switches may be required beyond those used to perform the restoration service. This includes switching feeders in the same substation or for substations that do not have any direct connection to the faulted feeder. These operations can cause discomfort, losses and dissatisfaction among consumers, as well as a negative reputation for the energy company. The purpose of this thesis is to develop a heuristic for reconfiguration of a distribution network, upon the occurrence of a failure in this network, making the switching only for feeders directly involved in this specific failed segment, considering that the switching applied is related exclusively to the isolation of failed sections and bars, as well as to supply electricity to the islands generated by the condition, with significant reduction in the number of applications of load flows, due to the use of sensitivity parameters for determining voltages and currents estimated on bars and lines of the feeders directly involved with that failed segment. A comparison between this process and classical methods is performed for different test networks from the literature about networks reconfiguration